Genetic variability of the inflammatory response. I. The -511 C/T IL1β polymorphism in different Peruvian subpopulations - Acosta, Oscar (2012)
Abstract The -511 citosyne/thymine (-511 C/T) polymorphism in the promoter region of human interleukin 1B (IL1β) gene is associated to differential cytokine synthesis and immuno-inflammatory response in obesity, dyslipidemias, cardiopathies, cancer, infections, other diseases, nutritional intervention and drug treatment. Objectives: To determine allelic and genotypic frequencies of -511 C/T polymorphism in the IL1β gene polymorphism in different Peruvian subpopulations. Design: Descriptive, cross-sectional study. Settings: Faculties of Human Medicine, Universidad Nacional Mayor de San Marcos and Universidad San Martin de Porres, Lima, Peru. Participants: Peruvian subjects. Interventions: Genomic DNA was extracted from 168 individuals from Lima (23 mestizos), 33 Amazonians (20 Pucallpa and 13 Amazonas) and 112 Andeans (12 Ancash, 10 Cajamarca, 18 Huarochiri-Lima, 25 Puno-Taquile, 25 Puno-Uros and 22 Puno-Anapia) according to standard methodology and amplification using PCR-RFLP technique. PCR products were digested with AvaI restriction enzyme and fragments were separated by 2% agarose gel electrophoresis and ethidium bromide stain. Main outcomes measures: Allelic and genotypic frequencies of the -511 C/T polymorphism in the IL1β gene. Results: CC=0,024, CT=0,369, and TT=0,607 genotypes frequencies were found, consistent with Hardy-Weinberg equilibrium, as well as alleles frequencies C = 0,208, and T= 0,792. The frequency of (mutant) T allele was very high in Puno-Uros (0,940) and low in Lima-mestizos (0,609). Comparison of genotypes (TT versus CT+CC) and alleles (T versus C) showed significant differences (p <0.01) between pairs Lima-mestizos and Puno-Uros and Puno-Taquile. Differences were significant (p <0.001) when compared to other world populations. Conclusions: T allele of IL1β gene -511 polymorphism related to increased production of the cytokine was frequent in these Peruvian subpopulations. Because of these differences, it is important to consider ethnicity in association studies and risk of this gene, factor of inflammatory response in obesity, dyslipidemias, cardiopathies, cancer, infections, other diseases, nutritional intervention and drug treatment.